Rogaratinib: A potent and selective pan‐FGFR inhibitor with broad antitumor activity in FGFR‐overexpressing preclinical cancer models. Issue 5 (13th March 2019) - Grünewald, Sylvia; Politz, Oliver; Bender, Sebastian; Héroult, Mélanie; Lustig, Klemens; Thuss, Uwe; Kneip, Christoph; Kopitz, Charlotte; Zopf, Dieter; Collin, Marie‐Pierre; Boemer, Ulf; Ince, Stuart; et al.
Abstract : Aberrant activation in fibroblast growth factor signaling has been implicated in the development of various cancers, including squamous cell lung cancer, squamous cell head and neck carcinoma, colorectal and bladder cancer. Thus, fibroblast growth factor receptors (FGFRs) present promising targets for novel cancer therapeutics. Here, we evaluated the activity of a novel pan‐FGFR inhibitor, rogaratinib, in biochemical, cellular and in vivo efficacy studies in a variety of preclinical cancer models. In vitro kinase activity assays demonstrate that rogaratinib potently and selectively inhibits the activity of FGFRs 1, 2, 3 and 4. In line with this, rogaratinib reduced proliferation in FGFR‐addicted cancer cell lines of various cancer types including lung, breast, colon and bladder cancer. FGFR and ERK phosphorylation interruption by rogaratinib treatment in several FGFR ‐amplified cell lines suggests that the anti‐proliferative effects are mediated by FGFR/ERK pathway inhibition. Furthermore, rogaratinib exhibited strong in vivo efficacy in several cell line‐ and patient‐derived xenograft models characterized by FGFR overexpression. The observed efficacy of rogaratinib strongly correlated with FGFR mRNA expression levels. These promising results warrant further development of rogaratinib and clinical trials are currently ongoing (ClinicalTrials.gov Identifiers: NCT01976741, NCT03410693, NCT03473756). Abstract : What's new? Deregulated fibroblast growth factor receptor (FGFR) signaling is involved in tumorigenesis and cancer progression. Here, the authors report on a novel pan‐FGFR inhibitor, rogaratinib, that potently and highly selectively prevents the activity of FGFRs 1, 2, 3, and 4. Rogaratinib inhibits cell proliferation in various FGFR‐addicted cancers in vitro, including colon, lung, and bladder cancer. Rogaratinib also exhibits strong in vivo efficacy in several cell line‐ and patient‐derived xenograft models characterized by FGFR mRNA overexpression with good tolerability. Altogether, these data warrant the further development of rogaratinib for treatment of cancers with FGFR alterations, and clinical trials are currently ongoing.